Smith & Keenan's Law for Business - Keenan, Denis J.; Smith, Kenneth, 1910-1966. (Harlow : Pearson/Longman, 2006)
The 13th edition of this title covers key areas of contract, sale of goods, consumer credit, employment and company law, and now includes material on the English legal system and business litigation, of particular interest to business, accounting and finance students.
Previous ed.: 2003.
Includes bibliographical references and index.
Keywords: Business law -- Wales; Business law -- England; Law